Factors Associated with Nurse Preparedness in Handling Disaster Victims in Central Sulawesi - Ra'bung, Alfrida Semuel; Tampake, Rina; Lenny, Lenny; Wartana, I Kadek (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Several factors influence nurses' preparedness in handling disaster victims. This study aims to identify the factors associated with nurses' preparedness to manage Central Sulawesi disaster victims. Conducted between April and July 2023, this cross-sectional quantitative study involved 124 nurses from Undata Hospital, Anutapura Hospital, Madani Hospital, Bhayangkara Hospital, and Dr. Sindhu Trisno Hospital, selected through total sampling. Preparedness was measured using the Disaster Preparedness Evaluation Tool (DPET). At the same time, knowledge, attitudes, and experiences in disaster management were assessed with the Knowledge, Attitude, and Practices of Disaster Management (KAP DM) questionnaire. Data were analyzed using chi-square and linear regression tests. The chi-square results indicated significant relationships between preparedness and knowledge (p=0.004), attitude (p=0.045), length of service (p=0.037), participation in disaster training (p=0.004), and experience in disaster management (p=0.028). At the same time, education level showed no significant relationship (p = 0.075). Linear regression revealed that knowledge had the strongest influence on preparedness. The study concludes that knowledge, attitudes, length of service, disaster training, and disaster management experience are key factors affecting nurses' preparedness. It is recommended that emergency nurses regularly participate in disaster-related training to enhance their ability to provide timely medical assistance, thereby reducing disaster-related mortality.